2001
DOI: 10.1104/pp.125.2.828
|View full text |Cite
|
Sign up to set email alerts
|

Urea Is a Product of Ureidoglycolate Degradation in Chickpea. Purification and Characterization of the Ureidoglycolate Urea-Lyase

Abstract: A ureidoglycolate-degrading activity was analyzed in different organs of chickpea (Cicer arietinum). Activity was detected in all the tissues analyzed, but highest levels of specific activity were found in pods, from which it has been purified and characterized. This is the first ureidoglycolate-degrading activity that has been purified to homogeneity from any photosynthetic organism. Only one ureidoglycolate-degrading activity was found during the purification. The enzyme was purified 1,500-fold, and specific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
44
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(46 citation statements)
references
References 26 publications
2
44
0
Order By: Relevance
“…Especially controversial is the nature of the ureidoglycolate-degrading reaction. From chickpea (Cicer arietinum) and common bean (Phaseolus vulgaris), enzymes were purified that, in contrast to UAH, cleave ureidoglycolate to glyoxylate and urea (Muñoz et al, 2001(Muñoz et al, , 2006. Consistently, it was reported that in soybean, half of the nitrogen from allantoate was released as urea, presumably during ureidoglycolate degradation (Todd and Polacco, 2004).…”
mentioning
confidence: 79%
“…Especially controversial is the nature of the ureidoglycolate-degrading reaction. From chickpea (Cicer arietinum) and common bean (Phaseolus vulgaris), enzymes were purified that, in contrast to UAH, cleave ureidoglycolate to glyoxylate and urea (Muñoz et al, 2001(Muñoz et al, , 2006. Consistently, it was reported that in soybean, half of the nitrogen from allantoate was released as urea, presumably during ureidoglycolate degradation (Todd and Polacco, 2004).…”
mentioning
confidence: 79%
“…UGL or UGAH), with one predominating over the other. For example, in soybean, ureidoglycolate catabolism was approximately 95% via UGAH and approximately 5% via UGL; thus, urease did not appear to be essential for ureide catabolism in this species (Stebbins and Polacco, 1995), whereas in chickpea (Cicer arietinum) UGL appears to be the predominant path (Munoz et al, 2001). The accumulation of ureidoglycolate and quantitative reduction in urea from Ni-D foliage suggests that the UGL activity is being impaired.…”
Section: Ureidesmentioning
confidence: 99%
“…Additionally, the accumulation of ureidoglycolate also suggests either that pecan might not possess the second pathway for the catabolism of ureidoglycolate or that the activity of UGAH is also being impaired by Ni deficiency. Ureidoglycolase is a metalloenzyme whose activity is inhibited by EDTA and enhanced by several different bivalent cations (Munoz et al, 2001). It is possible that one of these metal components is Ni.…”
Section: Ureidesmentioning
confidence: 99%
See 2 more Smart Citations